Measurement and simulation of electrical resistivity of cement-based materials by using embedded four-probe method. (28th November 2022) - Liang, Siming; Du, He; Zou, NingYu; Chen, Yuxuan; Liu, Yuhang
Highlights: An embedded four-probe method is used to measure electrical resistivity of mortars. A FE analysis is done to verify the feasibility of the embedded four-probe method. Differential scheme predicts well the electrical resistivity of cement mortars. Abstract: The electrical resistivity of cement-based materials is an important index that can be used for designing durable, multifunctional, and smart concrete structures. However, the measurement and prediction of electrical resistivity are far from being well addressed for cement-based materials. In this study, a modified four-probe test using embedded fine copper rods as electrodes was developed to measure the electrical resistivity of cement-based materials. A coupled thermal-electrical analysis was conducted to verify the feasibility of the modified four-probe method. The simulated results show that a linear relation between the electrical resistivity and the apparent electrical resistance. The contact resistance of the interface between the specimen and the electrodes has little effect on the electrical resistivity. The applied voltage ranging from 4 V to 28 V has a minor influence on the measured electrical resistivity. The electrical resistivity of the specimens cured under standard condition is greater than that under sealed condition. The electrical resistivity of cement-based materials cured under both sealed and standard conditions increases with increasing curing age. A higher volume fraction of sand contributes significantly to a higher electrical resistivity of cement-based materials. Moreover, the homogenization results indicate that the differential scheme predictions coincide quite well with the measured electrical resistivity of cement-based materials with a wide range of sand volume fractions (0%∼60%). The Voigt scheme, the self-consistent scheme, and the Mori-Tanaka scheme can predict well the electrical resistivity of cement-based materials with a low volume fraction of sand (<20%), but fail to give a good prediction at a higher sand content.